Pengaruh Implementasi Pemisahan Kelas Laki – Laki Dan Perempuan Terhadap Self Confidence Dan Motivasi Belajar Siswa Pada Pembelajaran Fikih Di Mtsn 1 Payakumbuh - Hayatul Khairi; Afrinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This associative quantitative research aims to test the effect of the policy on students' self-confidence and learning motivation, both partially and simultaneously. The low self-confidence and learning motivation of students in learning Fiqh at MTsN 1 Payakumbuh, so the madrasah implemented a class separation policy between male and female students to create a conducive learning environment. Using proportional random sampling techniques to determine samples and questionnaires as data collection instruments, statistical analysis was carried out through simple linear regression tests and Multivariate Analysis of Variance (MANOVA) with the help of IBM SPSS Statistics. The results of the study showed that: (1) the implementation of class separation between boys and girls had a positive and significant effect on students' self-confidence with a significance value of 0.000 <0.05, the regression equation Y₁ = 42.965 + 0.251X, and a coefficient of determination (R²) of 0.114, which means that the implementation of class separation contributed 11.4% to students' self-confidence; (2) the implementation of class separation between boys and girls has a positive and significant effect on student learning motivation with a significance value of 0.000 < 0.05, the regression equation Y₂ = 22.733 + 0.470X, and a coefficient of determination (R²) of 0.380, which means that the implementation of class separation contributes 38% to student learning motivation; and (3) the implementation of class separation between boys and girls simultaneously has a significant effect on student self-confidence and learning motivation, as indicated by the MANOVA test results with a significance value of Wilks' Lambda of 0.000 < 0.05. Based on these results, it can be concluded that the policy of class separation between boys and girls is effective in increasing student self-confidence and learning motivation, with a stronger influence on the motivational aspect. Therefore, this policy is worth maintaining and should be supported by more active, participatory, and student-centered learning innovations so that the benefits obtained can be more optimal.